2022
DOI: 10.15388/sw.2022.12.14
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Internality and Self-development of Psychology Students: the Effect of Optimistic Attributional Style

Abstract: The article represents the research of relationship between internality and self-development in the case of the different levels of optimistic attributional styles. The sample consists of psychology students of Ukraine. The strong positive impact of internality on self-development under conditions of medium optimistic attribution has been revealed. A decrease has also been set in self-development of psychology students with high internality in the case of a highly developed optimistic attributional style. It h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
2
0
3
Order By: Relevance
“…In scientific literature there are numerous studies which conceptually outlined methodological fundamentals of selfpresentation , theoretically substantiated topical tendencies, regularities and determinants of selfdevelopment (Ketler-Mytnytska & Shevchenko, 2022;Lopez et al, 2023), elucidated the current state of the problem sweeping social and the Internet (Kleinman at al., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In scientific literature there are numerous studies which conceptually outlined methodological fundamentals of selfpresentation , theoretically substantiated topical tendencies, regularities and determinants of selfdevelopment (Ketler-Mytnytska & Shevchenko, 2022;Lopez et al, 2023), elucidated the current state of the problem sweeping social and the Internet (Kleinman at al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…2). The prevalence of medium and high parameters of self-deceit and managing impressions in combination with sociability, Дискусія У науковій літературі є безліч досліджень які концептуально окреслили методологічні основи самопрезентації , теоретично обґрунтували актуальні тенденції і з'ясовані закономірності та детермінанти саморозвитку (Ketler-Mytnytska, Shevchenko, 2022;Lopez et al, 2023), висвітлили сучасний стан проблеми, який огорнув соціальні мережі та всемережжя (Kleinman at al., 2023).…”
Section: Antonina Hrys* Oksana Pavliukunclassified
“…We discovered an incredibly large number of studies in the scientific literature that illuminate and operationalize an individual's development and self-development at ontogenetic stages (Kuzikova, 2023;, in professional formation (Shevchenko, 2022), relating to selfregulation, self-creation, and self-actualization of an individual (Baumeister et al 2003). Permanent dispositional self-development as a readiness and inclination to develop is a powerful preventive measure against burnout among socioeconomic profile specialists and burnout among respondents from other fields of activity (Jezzini-Martinez et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The ascertaining research strategy identified a variety of changes that reflect indicators of the development of structural components of self-confidence: self-respect, self-Personal Determination of Self-Confidence in Youth аналізування соціальної ситуації розвитку юнацького віку та узгодження зі структурою довіри до себе. До вказаних детермінант обґрунтовано віднесено: почуття власної гідності; адекватну самооцінку; інтернальність суб'єктивного контролю; мотивацію досягнення успіху; віру у власну самоефективність (Rogers, 1995;Рибалка, 2011;Єрмакова, 2023;Шевченко, Кузьмич, 2022;Ketler-Mytnytska et al, 2022;Dahlan, 2019;Green et al, 2022).…”
Section: Methodsunclassified
“…Дослідженню особистісних детермінант довіри до себе в осіб юнацького віку передувало їх обґрунтування на основі теоретичного of self-confidence. The indicated determinants were reasonably assigned to: dignity; adequate self-esteem; internality of subjective control; motivation for success; belief in one's own selfefficacy (Rogers, 1995;Rybalka, 2011;Yermakova, 2023;Shevchenko, Kuzmych, 2022;Ketler-Mytnytska et al, 2022;Dahlan, 2019;Green et al, 2022).…”
Section: Nataliia Shevchenkounclassified